THE EFFECT OF APPLYING COOPERATIVE LEARNING MODEL ON STUDENT COMPETENCE: LITERATURE STUDY ABOUT STUDENT FACILITATOR AND EXPLAINING - Khairina Khairina; Heffi Alberida; Rahmadhani Fitri; Ardi Ardi (Universitas Negeri Padang, 2021)
Achievement and success in learning depends on several aspects. One aspect that really influences is how a teacher implements learning. The background of the writing of this article is based on the results of observations and interviews at school which show that the learning process still tends to be teacher-centered, and this also has an impact on the learning competences. One way that can be used to demand the activeness of students is by applying the learning model. Based on the literature study that has been conducted, the writer found a suitable learning model to overcome the problems found, namely the Student Facilitator and Explaining type of cooperative learning model. This type of research is a literature study using descriptive analysis. Based on the literature study conducted, learning using the Student Facilitator and Explaining type of cooperative learning model can improve the learning competence of students. It makes students as facilitators and is invited to think so that it will result in a deeper and more interesting exchange of information and lead to self-confidence in students. It is very helpful to improve the learning competence of students both in the aspects of attitudes, knowledge and skills.